Vancomycin-resistant Enterococcus sequence type 1478 spread across hospitals participating in the Canadian Nosocomial Infection Surveillance Program from 2013 to 2018. (10th March 2022) - Kleinman, David R.; Mitchell, Robyn; McCracken, Melissa; Hota, Susy S.; Golding, George R.; Smith, Stephanie W.
Abstract: Objective: To analyze the spread of a novel sequence type (ST1478) of vancomycin-resistant Enterococcus faecium across Canadian hospitals. Design: Retrospective chart review of patients identified as having ST1478 VRE bloodstream infection. Setting: Canadian hospitals that participate in the Canadian Nosocomial Infection Surveillance Program (CNISP). Methods: From 2013 to 2018, VRE bloodstream isolates collected from participating CNISP hospitals were sent to the National Microbiology Laboratory (NML). ST1478 isolates were identified using multilocus sequence typing, and whole-genome sequencing was performed. Patient characteristics and location data were collected for patients with ST1478 bloodstream infection (BSI). The sequence and patient location information were used to generate clusters of infections and assess for intrahospital and interhospital spread. Results: ST1478 VRE BSI occurred predominantly in a small number of hospitals in central and western Canada. Within these hospitals, infections were clustered on certain wards, and isolates often had <20 single-nucleotide variants (SNV) differences from one another, suggesting a large component of intrahospital spread. Furthermore, some patients with bloodstream infections were identified as moving from one hospital to another, potentially having led to interhospital spread. Genomic analysis of all isolates revealed close relatedness between isolates at multiple different hospitals (<20 SNV) not predicted from our epidemiologic data. Conclusions: Both intrahospital and regional interhospital spread have contributed to the emergence of VRE ST1478 infections across Canada. Whole-genome sequencing provides evidence of spread that might be missed with epidemiologic investigation alone.